PSYCHOLOGICAL FEATURES OF THE EDUCATIONAL MOTIVE IN ADOLESCENCE (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
today, most people feel Wayward or isolated. These emotions affect a person's health and life. Pathlessness and isolation are not only personal problems, but also social phenomena. In this article, we will talk in detail about what pathlessness and isolation are, their causes, consequences and ways to overcome